On the Ophioniformes group (Hymenoptera: Ichneumonidae) from Kerman province with six new records to Iran - Negar Bahremand; Mohammad Khayrandish; Abbas Mohammadi-Khoramabadi; Matthias Reidel (Journal of Insect Biodiversity and Systematics, 2022)
View on Scopus The fauna of the Ophioniformes group (Hym.: Ichneumonidae) was studied in the southern part of Kerman province, Iran during 2014–2015. Four localities (Faryab, Jiroft, Maskoon and Sarbijan) have been surveyed using eight Malaise traps. Two traps were operated in each location. A total of 135 specimens of the Ophioniformes group have been collected and identified representing 27 species into seven subfamilies and 17 genera. One genus (i.e. Meloboris Holmgren, 1859) and six species are reported from Iran for the first time: Diadegma kyffhusanae Horstmann, 1973, Hyposoter barretti (Bridgman, 1881), Hyposoter caudator Horstmann, 2008, Meloboris collector (Thunberg, 1822), Sinophorus pleuralis (Thomson, 1887) and Mesochorus arenarius (Haliday, 1838). Fifteen species are newly recorded from Kerman province. The biographical and altitudinal range distribution, as well as adult flight period of the identified species, are also discussed.